2019
DOI: 10.1007/s00107-019-01465-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased yield of finger jointed structural timber by accounting for grain orientation utilizing the tracheid effect

Abstract: Finger joints in structural timber and glulam lamellae are often used to enable production of long members or to allow for re-connection of parts of a member after removal of weak sections. According to the European Standard EN 15497, certain margins are required between knots and a finger joint in structural timber, which means that a considerable amount of clear wood becomes waste when finger joints are applied. The purpose of this paper was to investigate the possibility of reducing the quantity of waste us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…To apply these advanced wood material models successfully to timber, the internal morphology of timber needs to be known and modeled in detail, at least in the proximity of the governing defects. Promising research regarding the determination of the complete 3D orientation of the wood grain and approaches to model the complete morphology of timber is in progress (Guindos and Guaita 2013;Lukacevic and Fnssl 2014;Olsson and Oscarsson 2014;Jenkel and Kaliske 2014;Füssl et al 2014). These approaches which in a figurative sense model "the wood within the timber" might improve the knowledge of the effects of defects in the near future.…”
Section: Wood and Timbermentioning
confidence: 99%
“…To apply these advanced wood material models successfully to timber, the internal morphology of timber needs to be known and modeled in detail, at least in the proximity of the governing defects. Promising research regarding the determination of the complete 3D orientation of the wood grain and approaches to model the complete morphology of timber is in progress (Guindos and Guaita 2013;Lukacevic and Fnssl 2014;Olsson and Oscarsson 2014;Jenkel and Kaliske 2014;Füssl et al 2014). These approaches which in a figurative sense model "the wood within the timber" might improve the knowledge of the effects of defects in the near future.…”
Section: Wood and Timbermentioning
confidence: 99%
“…This name derives from the first observations on softwoods (Nyström 2003) (Simonaho et al 2002) and , which is based on the anisotropic scattering of concentrated laser light projected onto the wood surface (Daval et al 2015;Purba et al 2020) . (Olsson et al 2019) and (Besseau 2021) suggested using fiber orientation measured from such scanners to ensure the finger-joint strength rather than knot diameter (d) or distance to knot. Both authors offering promising prospects for reducing material waste and improving the reliability of finger-jointed lamellas.…”
Section: Oak Timber Cross-cutting Based On Fiber Orientation Scanning...mentioning
confidence: 99%
“…Both authors offering promising prospects for reducing material waste and improving the reliability of finger-jointed lamellas. (Olsson et al 2019) defined a threshold of 8° to determine quantitatively when fibers are "approximately parallel to the axis of the board" as it is stated in (NF EN 14080 2013) standard. They found out that wasted material when cross-cutting Norway spruce can be decreased from 7.4% to 4% when applying a rule based on a minimum distance of 1.5 times d from the knot and a fiber deviation below 8°.…”
Section: Oak Timber Cross-cutting Based On Fiber Orientation Scanning...mentioning
confidence: 99%
“…For example, according to several experiments on the flexural behaviour of CLT panels conducted by Navaratnam et al [6], finger joint failure is one of the most common failure modes observed in the tests. As a result, several design factors related to finger joints such as finger length, tip width, pitch, and finger slope should be considered in the production of an EWP to assure its structural performance [6][7][8]. Several studies have been conducted to investigate the effect of finger joint design parameters on structural performance by performing experiments or using the finite element method (FEM).…”
Section: Introductionmentioning
confidence: 99%